Hematological parameters and remission induction of childhood acute lymphoblastic leukemia - Roro Rukmi Windi Perdani; Bambang Sudarmanto (Indonesian Pediatric Society, 2018)
Background High-risk acute lymphoblastic leukemia (ALL) is one of the most common childhood malignancies in Indonesia. Many factors can inhibit the induction of remission. Hematological parameters are usually not normal. Identification of corresponding factors is important to increase the likelihood of successful inductions. Objective To assess for associations between hematological parameters and induction of remission in children with acute lymphoblastic leukemia. Methods Data were collected from medical records of ALL patients hospitalized in the Pediatric Ward at Dr. Kariadi Hospital from May 2014 – May 2016. Dependent variables were hemoglobin, leukocytes, platelets, and absolute neutrophil count (ANC) levels; the independent variable was induction of remission. Results Out of 55 patients, 33 (60%) had anemia, 6 (10.9%) had leukocytosis, and 1 (1.8%) had hyperleukocytosis, whereas 9 (34.5%) had leukopenia and 29 (52,7%) had normal leukocyte levels. Thirty-one subjects (56.4%) had thrombocytopenia, 15 (27.3%) had thrombocytosis, and only 9 (16.4%) patients had normal platelet counts. There were 29 (52.7%) with absolute ANC > 500, whereas 26 (47.3%) had ANC level ≤ 500. Most patients (80%) experienced remission induction, while 20% did not. There were significant associations between ANC level and induction of remission (P=0.010) as well as between platelet level and induction of remission (P= 0.033). Regression logistic test revealed that ANC level ≤ 500 was associated with a 7-fold lower remission event compared to ANC level > 500 (RR 7.147; 95%CI 1.38 to 37.14). Conclusion Lower ANC level (≤ 500) was significantly associated with lower remission compared to higher ANC level (> 500).